Blockade of 5-HT2 receptors suppresses motor unit firing and estimates of persistent inward currents during voluntary muscle contraction in humans - Goodlich, Benjamin I.; Del Vecchio, Alessandro; Horan, Sean A.; Kavanagh, Justin J. (The Journal of Physiology, 2023)
Abstract: Serotonergic neuromodulation contributes to enhanced voluntary muscle activation. However, it is not known how the likely motoneurone receptor candidate (5-HT2) influences the firing rate and activation threshold of motor units (MUs) in humans. The purpose of this study was to determine whether 5-HT2 receptor activity contributes to human MU behaviour during voluntary ramped contractions of differing intensity. High-density surface EMG (HDsEMG) of the tibialis anterior was assessed during ramped isometric dorsiflexions at 10, 30, 50 and 70% of maximal voluntary contraction (MVC). MU characteristics were successfully extracted from HDsEMG of 11 young adults (four female) pre- and post-ingestion of 8 mg cyproheptadine or a placebo. Antagonism of 5-HT2 receptors caused a reduction in MU discharge rate during steady-state muscle activation that was independent of the level of contraction intensity [P < 0.001; estimated mean difference (∆) = 1.06 pulses/s], in addition to an increase in MU derecruitment threshold (P < 0.013, ∆ = 1.23% MVC), without a change in force during MVC (P = 0.652). A reduction in estimates of persistent inward current amplitude was observed at 10% MVC (P < 0.001, ∆ = 0.99 Hz) and 30% MVC (P = 0.003, ∆ = 0.75 Hz) that aligned with 5-HT changes in MU firing behaviour attributable to 5-HT2 antagonism. Overall, these findings indicate that 5-HT2 receptor activity has a role in regulating the discharge rate in populations of spinal motoneurones when performing voluntary contractions. This study provides evidence of a direct link between MU discharge properties, persistent inward current activity and 5-HT2 receptor activity in humans. (Figure presented.). Key points: Activation of 5-HT receptors on the soma and dendrites of motoneurones regulates their excitability. Previous work using chlorpromazine and cyproheptadine has demonstrated that the 5-HT2 receptor regulates motoneurone activity in humans with chronic spinal cord injury and non-injured control subjects. It is not known how the 5-HT2 receptor directly influences motor unit (MU) discharge and MU recruitment in larger populations of human motoneurones during voluntary contractions of differing intensity. Despite the absence of change in force during maximal voluntary dorsiflexions, 5-HT2 receptor antagonism caused a reduction in MU discharge rate during submaximal steady-state muscle contraction, in addition to an increase in MU derecruitment threshold, irrespective of the submaximal contraction intensity. Reductions in estimates of persistent inward currents after 5-HT2 receptor antagonism support the viewpoint that the 5-HT2 receptor plays a crucial role in regulating motor activity, whereby a persistent inward current-based mechanism is involved in regulating the excitability of human motoneurones.
CRIS-Team Scopus Importer:2023-03-17
Keywords: high-density electromyography; monoamine; motoneurone; neuromodulation; persistent inward current